Implementation of the Farmerâ€™s Empowerment Program by Rural Agribusiness Development (A Case Study in Mulyodadi Village Wonoayu Subdistrict Sidoarjo Regency) - Desy Gigih Pratiwi; Sanggar Kanto; Siti Kholifah (Sekolah Pascasarjana Universitas Brawijaya, 2018)
The fundamental farmerâ€™s problem is accessing capital resources. Rural Agribusiness Development (called PUAP) is a form of facilitation of venture capital assistance for members of farmer groups are coordinated by Gapoktan. The aim of this research was to: (1) describe and review the implementation of the farmerâ€™s empowerment program by rural agribusiness development; (2) identify and explore factors that influence the effectiveness the implementation of rural agribusiness development; (3) review and formulate the reconstruction of farmerâ€™s empowerment design model by rural agribusiness development. The research is a qualitative case study type in Mulyodadi Village, Wonoayu Subdistrict, Sidoarjo Regency. Data were collected and searched by using data collection methods by observation, interviews and documentation. Data is processed using by interactive model of analysist from the field research results. Researcher adopts the framework of ACTORS by Sarah Cook dan Steve Macaulay. The conclusion of this research is needed to evaluation and improve the implementation of rural agribusiness development which has not been implemented properly and less effective. Phenomenons behind â€œhas not been implemented properly and less effectiveâ€ are the difference between the goals and outcomes of the program irrelevant. There are several things that cause the implementation of rural agribusiness development in Mulyodadi is less effective, among other: Gapoktan in Sidoarjo regency has not been appointed by the regent and non-comprehension of regulatory substance by implementing agency. Results of this research need to redesign model of the farmerâ€™s empowerment program to interpreting the goals and outcomes of the program to be on target by adding new empowerment activities to complete the problems of PUAP program.